Prokopenko A. V. Сonflict strategies of a politician in the aspect of translation strategies (on the basis of Аmerican political interview) - Prokopenko A. V. (Philological Treatises, 2020)
The research deals with the strategies of political communication and translation strategies. Attention is being focused upon conflict tactics of a politicians and their speech representation in the aspect of translation strategies.